Analysis of heat transfer and water flow with phase change in saturated porous media by bond-based peridynamics. (April 2022) - Nikolaev, Petr; Sedighi, Majid; Jivkov, Andrey P; Margetts, Lee
Highlights: A Peridynamic formulation for heat transfer with phase change is presented. Bond-based peridynamics is shown to provide robust solution to phase change process. Melting a frozen inclusion by water flow is analysed by the new coupled model. The new formulation allows for accurate prediction of the phase change interfaces. Abstract: A wide range of natural and industrial processes involve heat and mass transport in porous media. In some important cases the transported substance may undergo phase change, e.g. from liquid to solid and vice versa in the case of freezing and thawing of soils. The predictive modelling of such phenomena faces physical (multiple physical processes taking place) and mathematical (evolving interface with step change of properties) challenges. In this work, we develop and test a non-local approach based on bond-based peridynamics which addresses the challenges successfully. Our formulation allows for predicting the location of the interface between phases, and for calculating the temperature and pressure distributions within the saturated porous medium under the conditions of pressure driven water flow. The formulation is verified against existing analytical solutions for 1D problems, as well as finite element transient solutions for 2D problems. The agreement found by the verification exercise demonstrates the accuracy of the proposed methodology. The detailed coupled description of heat and hydraulic processes can be considered as a critical step towards a thermo-hydro-mechanical model, which will allow, for example, description of the hydrological behaviour of permafrost soils and the frost heave phenomenon.